Peran Kepemimpinan Dalam Meningkatkan Kualitas Pengambilan Keputusan Organisasi - Moch Bintang Nabawi; Sayid Mustafa Malusu; Aos Kuswandi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
. Leadership within organizations is no longer confined to structural authority but has evolved into a strategic function that influences the entire organizational process, including decision-making. This article aims to comprehensively analyze how leadership roles contribute to improving the quality of organizational decision-making. The research adopts a literature review method by examining various scholarly journals and relevant references to identify key factors linking leadership quality and decision effectiveness. The findings reveal that visionary, communicative, and participative leadership significantly enhances decision quality. Seven main aspects were identified: (1) leadership as a determinant of organizational direction, (2) the importance of analytical and interpersonal skills, (3) the leader as the center of information and organizational symbol, (4) leadership styles shaping motivation and work ethics, (5) leadership as a relational activity, (6) exemplary leadership in driving organizational transformation, and (7) the correlation between leadership quality and commitment to decision implementation. These findings emphasize that long-term organizational success is not only driven by strategy and resources, but also by leadership quality that fosters trust, manages team dynamics, and makes decisions that are inclusive and adaptive to environmental changes. This article recommends that organizations invest in developing leadership competencies that go beyond technical skills, encompassing moral, social, and psychological dimensions of leadership.